(untitled) (Journal of Informatics Education and Research, 2026)
Artificial Intelligence (AI) has emerged as a transformative force across industries, revolutionizing the way organizations make business decisions. This research investigates the adoption, readiness, and challenges of integrating AI technologies within business enterprises in Mumbai. Drawing on quantitative analysis from 403 organizations, the study explores factors influencing AI integration, including infrastructure availability, leadership commitment, regulatory readiness, and openness to innovation. Findings reveal that while many organizations recognize AI’s potential to enhance decision-making and operational efficiency, significant barriers persist particularly in integrating AI systems with legacy IT infrastructure and ensuring scalability of AI models. The study emphasizes that AI should be viewed not merely as a technological upgrade but as a strategic enabler for intelligent, data-driven decision-making. Recommendations include strengthening leadership commitment, investing in adaptable infrastructure, and fostering a culture of innovation to fully harness AI’s potential in business decision-making.